An introduction to statistical issues and methods in metrology for physical science and engineering. - Vardeman, Stephen (Journal of Quality Technology)
This article provides an overview of the interplay between statistics and measurement. Measurement quality affects inference from data collected and analyzed using statistical methods while appropriate data analysis quantifies the quality of measurements. This article brings material on statistics and measurement together in one place as a resource for practitioners. Both frequentists and Bayesian methods are discussed.